Protective actions of melatonin against heart damage during chronic Chagas disease - Oliveira, Luiz Gustavo Rodrigues; Kuehn, Christian Collins; dos Santos, Carla Domingues; Miranda, Mariza Abreu; da Costa, Cassia Mariana Bronzon; Mendonça, Vagner José; do Prado, José Clóvis (Elsevier, 2013)
Chronic cardiomyopathy is the most important clinical form of Chagas disease, and it is characterised by myocarditis that is associated with fibrosis and organ dysfunction. Alternative treatment options are important tools to modulate host immune responses. The main goal of this work was to evaluate the anti-inflammatory actions of melatonin during the chronic phase of Chagas disease. TNF-α, IL-10 and nitrite concentrations were evaluated as predictive factors of immune modulation. Creatine phosphokinase-MB (CK-MB), cardiac inflammatory foci and heart weight were assessed to evaluate the efficacy of the melatonin treatment. Male Wistar rats were infected with 1 × 105 blood trypomastigotes of the Y strain of Trypanosoma cruzi and kept untreated for 60 days to mimic chronic infection. After this period, the rats were orally treated with melatonin 50 mg/kg/day, and the experiments were performed 90, 120, and 180 days post-infection. Melatonin treatment significantly increased the concentration of IL-10 and reduced the concentrations of NO and TNF-α produced by cardiomyocytes. Furthermore, it led to decreased heart weight, serum CK-MB levels and inflammatory foci when compared to the untreated and infected control groups. We conclude that melatonin therapy is effective at protecting animals against the harmful cardiac inflammatory response that is characteristic of chronic T. cruzi infection. © 2013 Elsevier B.V. All rights reserved.
Keywords: CK-MB; IL-10; Melatonin; Nitric oxide; TNF-α; Trypanosoma cruzi